The effect of innovation in achieving the competitive advantage in the industrial companies operating in Hebron governorate - Qabaja, Adnan Abdel Majeed; Jaradat, Nasser Mohammed Saud (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed at identifying the impact of innovation on achieving the competitive advantage in industrial companies operating in Hebron governorate, the study adopted the descriptive-analytical method for research purposes. The target population consisted of all industrial companies operating in Hebron governorate, Purposive sample of directors, board members, companies directors, heads and directors of departments in industrial companies, ( 80 ) questionnaires were distributed, (70) questionnaires returned for analysis, the study found 82.7% of the variation in competitive advantage is due to innovation in the companies under research, and that the increase of one unit of innovation in the field of the product has led to an increase in competitive advantage by 75.2% of this unit, and that the increase of one unit of innovation in the field of operation has led to An increase in competitive advantage by 83.3% of this unit. The study recommended that companies need to increase attention to the concept of innovation and competitive advantage to promote survival and growth in highly competitive markets, as well as the need to provide the right environment to create innovation and increase the allocation of scientific research by the companies under research.